Phytochemical profiling, in vitro biological activity, docking studies, and cytotoxicity assessments of Rondeletia odorata Jacquin: An unexplored plant of the coffee family - Khursheed, Anjum; Ahmad, Saeed; Saleem, Muhammad; Khan, Kashif-ur-Rehman; Khan, Jallat; Orhan, Ilkay Erdogan; Abaci, Nurten; Imran, Muhammad; Tauseef, Saba; Uddin, Reaz; Yawer, Mirza Arfan; Tousif, Muhammad Imran; et al. (Frontiers in Chemistry, 2022)
Rondeletia odorata is a flowering plant that belongs to the coffee family. As a rich source of polyphenols with significant antioxidant potential, R. odorata may have health benefits. Therefore, in the current work ethanolic extract of aerial parts and its hexane, ethyl acetate and butanol soluble fractions were analyzed for their antioxidant potential and various enzyme inhibition properties. Total phenol and flavonoid contents of the crude ethanol extract (ROE) and its n-hexane (ROH), ethyl acetate (ROEA), and n-butanol (ROB) fractions were determined spectrophotometrically, while metabolic profiling was established through UHPLC-MS analysis, which revealed the presence of 58 phytochemicals. Total phenolic and flavonoid contents of ROE extract were measured as 51.92 mg GAE/mg of dry extract and 52.35 mg QE/mg of the dry extract, respectively. In DPPH radical scavenging activity assay, ROE and ROEA showed highest potential with the values as 62.13 ± 0.62 and 76.31 ± 1.86%, respectively, comparable to quercetin (80.89 ± 0.54%). Similarly, in FRAP assay, same pattern of the activity was observed with ROE and ROEA, which displayed absorbance values of 1.32 ± 0.01 and 0.80 ± 0.02 at 700 nm, respectively, which are comparable (1.76 ± 0.02) with the reference compound quercetin, whereas the ROH showed maximum metal-chelating capacity (62.61 ± 1.01%) among all extracts and fractions. Antibacterial activity assay indicated that ROEA fraction was the most active against Serratia marcescens, Stenotrophomonas maltophilia, Bacillus subtilis, Klebsiella pneumonia, and Staphylococcus aureus, while rest of the fractions showed good to moderate activity. Enzyme inhibition assays showed that ROEA fraction exhibited highest activity with IC50 values of 2.78 ± 0.42 and 3.95 ± 0.13 mg/mLagainst urease and carbonic anhydrase (CA), respectively. Further the docking studies of some of the major compounds identified in the extract revealed a strong correlation with their inhibitory activity. All extracts and fractions were also tested for their thrombolytic activity and the ROB fraction showed a notable potential. Antiviral assay led to the remarkable outcomes. Thus, it can be inferred that aerial parts of R. odorata are potential source of bioactive components with several significant pharmacological activities.